An Teach Irish Housing Association leasing flyer - An Teach Irish Housing Association, ATHA (1995)
Flyer inviting property owners to entrust the management of their properties to An Teach. [Contact telephone number redacted on digital image.] Accompanying documentation dated 26 October 1995.